2020
DOI: 10.1007/s11121-020-01099-2
|View full text |Cite
|
Sign up to set email alerts
|

Ready, Willing and Able? An Investigation of the Theory of Planned Behaviour in Help-Seeking for a Community Sample with Current Untreated Depressive Symptoms

Abstract: Applying health behaviour change models, such as the theory of planned behaviour (TPB), to help-seeking for mental health problems can address the deficit in health care utilisation. However, previous studies largely focused on help-seeking intentions and not behaviour, which might be problematic due to the intention-behaviour gap. Hence, TPB and help-seeking were examined in a German community sample with current untreated depressive symptoms: 188 adults (M age = 50.34; SD = 16.19; 70.7% female) participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 39 publications
4
50
4
2
Order By: Relevance
“…With the TPB [60,61] subjective norms (items 1 to 4), attitudes (items 5 to 7) and perceived control (items 8 to 10) of help-seeking, theoretically based on the Theory of Planned Behaviour [1], is assessed. All items measuring subjective norms (α = .84) and perceived behavioural control (α = .74) were rated on a 7-point Likert scale from 1 = "strongly disagree" to 7 = "strongly agree".…”
Section: Help Seeking Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…With the TPB [60,61] subjective norms (items 1 to 4), attitudes (items 5 to 7) and perceived control (items 8 to 10) of help-seeking, theoretically based on the Theory of Planned Behaviour [1], is assessed. All items measuring subjective norms (α = .84) and perceived behavioural control (α = .74) were rated on a 7-point Likert scale from 1 = "strongly disagree" to 7 = "strongly agree".…”
Section: Help Seeking Measuresmentioning
confidence: 99%
“…Results showed that stigmatising attitudes were negatively associated with a perceived need for help [59] and the use of professional psychiatric and psychotherapeutic help (β = − 0.19, p = 0.08). Furthermore, the main predictor for health care utilisation was the intention to seek help, which explained 22-37% of the variance of actual help-seeking behaviour and was especially strong for seeking psychotherapeutic help (β = 0.31, p < 0.001 [60];). Additionally, further findings concerning the self-identification as mentally ill [57], as well as a subjective sense of illness [58] and their respective association with help-seeking intention and behaviour were considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intentions can lead to the implementation of the behaviour if the agent has the possibility of doing so, i.e., if the agent "can decide at will to perform or not perform the behaviour" [50]. Research focused on the intention-behaviour gap is vast and sometimes mixed (e.g., [57][58][59][60]). Previous studies have reported positive relationships between behavioural intention and actual behaviour in the construction sector [49,61].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…En la actualidad una de las teorías más utilizadas para explicar los factores que llevan a las personas a participar en el comportamiento en distintos contextos, biológicos (Li y Li, 2020), alimentación (Lwin, Malik y Lau, 2020), psicológicos (Tomczyk et al, 2020), informáticos (Yakasai y Jusoh, 2015), marketing (Justin, Ashwin y Jayesh, 2016), sostenibilidad (Savari y Gharechaee, 2020;Hao et al, 2020;Yang et al, 2019;Torres, Barreto y Rincón, 2015), es la Teoría del Comportamiento Planificado.…”
Section: Teoría Del Comportamiento Planificadounclassified